The influence of helicopter parenting on students self-efficacy and psychological well-being based on educational counseling perspective in madrasah tsanawiyah - Syafi'i Syafi'i; Evi Winingsih; Titin Indah Pratiwi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to determine the influence of helicopter parenting on self-efficacy and psychological well-being in Madrasah Tsanawiyah students. This study uses a quantitative approach with a correlation design, and data obtained from 210 students through a likert scale questionnaire. The results of the study showed that there were clear differences based on gender. In male students, helicopter parenting does not have a significant effect on self-efficacy or psychological well-being. In contrast, in female students a significant influence was found, which showed that the higher the level of helicopter parenting, the lower their levels of self-efficacy and psychological well-being. These findings indicate that female students are more vulnerable to the psychological impact of overly controlling parenting, especially in the context of faith-based schools that tend to impose strict moral norms. Further research is suggested to explore cultural and emotional factors that may influence the relationship between parenting and adolescent psychological development.